“Evaluación de las condiciones de trabajo en la empresa tecnoblock s. a. mediante el método lest, 2021” - Vergara Jaen, Douglas Alain (2021)
This research project was based on developing an evaluation of working conditions through the LEST method in the company TECNOBLOCK S.A located at Km. 14 Vía Quevedo – Ventanas, Parroquia San Carlos. Through the NTP 330 matrix, high-risk positions were identified, such as sawmill operator, sawmill receiver and sawmill supplier. Using the Ergoniza software tool used for ergonomic evaluation of jobs, the LEST methodology was used, which includes the study of working conditions through the evaluation of variables such as physical environment, physical load, working times and psychosocial aspects in order to obtain a global diagnosis. Consequently, as a result of the evaluation, it was shown that the physical environment and the physical load are those with the highest incidence and of a harmful nature present in the workplaces. Subsequently, a proposal for a comprehensive risk control plan was established with the aim of carrying out training, providing personal protective equipment with the purpose of reducing work accidents and / or occupational diseases and contributing to the improvement of the work environment Keywords: Working conditions, LEST method, physical environment, physical load, risk assessment